واقع وآفاق تطبيق التسويق الرقمي بالمؤسسات السياحية والفندقية دراسة حالة الشركة العالمية Tripadvisor.com - سيلم, مختار; عليان, فتحي (جامعة الوادي - University of Eloued, 2023)
This study aims to identify the reality and prospects for the application of digital marketing in tourism and hotel establishments, with a case study of the global company Tripadvisor.com, where the analytical descriptive approach was relied upon, which relies on analyzing data collected from various interested websites. The digital marketing by the company Tripadvisor.com is evident through the distinguished position occupied by the studied company among its competitors, as well as its increasing growth rates from year to year in all fields. Therefore, tourism and hotel establishments in all countries of the world and Algeria must adopt the digital marketing option as a strategic option for them. And take inspiration from the company's Tripadvisor.com experience
The reality and prospects of applying digital marketing in tourism and hotel establishments Tripadvisor.com Global Company Case Study
مقال
Keywords: التسويق الرقمي ; المؤسسات السياحية ; المؤسسات الفندقية ; المواقع الالكترونية ; شركة; Digital marketing, tourism establishments, hotel establishments, websites, Tripadvisor.com.